Effects of silencing NLRP3 gene on proliferation of psoriasis-like HaCaT cells and expressions of cytokines: N L R P 3 g e n e silencing impacts - An, Yuepeng; Yuan, Rui; Wang, Shanshan; Yang, Suqing; Zhang, Qing (Cellular and Molecular Biology, 2024)
We aimed to explore the effects of silencing NOD-like receptor protein 3 (NLRP3) on proliferation of psoriasis-like HaCaT cells and expressions of cytokines. HaCaT cells were treated with human keratinocyte growth factor (KGF) and were divided into KGF group, negative control group, NLRP3-RNAi group and control group. Cells proliferation was detected by CCK8, cell clone formation rate was detected by clone formation assay, distribution of cells cycle was detected by flow cytometry, expressions of cyclin B1 (Cyclin B1), cyclin-dependent kinase 2 (CDK2), Ki67 and proliferating cell nuclear antigen (PCNA) proteins were detected by Western blot, and levels of interleukin (IL)-17, IL-23, IL-6 and tumor necrosis factor α (TNF-α) were detected by enzyme-linked immunosorbent assay. Compared with control group, expressions of NLRP3 mRNA and protein, proliferation rate and clonal formation rate were increased in KGF group, percentage of cells in G0/G1 phase was decreased, percentage of cells in S phase was increased, expressions of Cyclin B1, CDK2, Ki67 and PCNA proteins were increased, and levels of IL-17, IL-23, IL-6 and TNF-α were increased. Compared with negative control group, expressions of NLRP3 mRNA and protein, proliferation rate and clonal formation rate were decreased in NLRP3-RNAi group, percentage of cells in G0/G1 phase was increased, percentage of cells in S phase was decreased, expressions of Cyclin B1, CDK2, Ki67 and PCNA proteins were decreased, and levels of IL-17, IL-23, IL-6 and TNF-α were decreased. Silencing NLRP3 gene can inhibit the proliferation of psoriasis-like HaCaT cells, arrest cell cycle, inhibit the expressions of cell proliferation-related proteins and reduce levels of pro-inflammatory factors.